The effects of rumen-protected tryptophan (RPT) on production performance and relevant hormones of dairy cows - Hui Ma; Songyang Yao; Libing Bai; Sarvvl Bai; Guoshi Liu (PeerJ, 2022)
Tryptophan is an essential amino acid that cannot be synthesized in mammals. Therefore, the dietary supply of tryptophan is critical for the health and production performance (e.g., milk) of mammals. In the present study, 36 lactating Holstein cows were used, of which 24 cows were in the rumen-protected tryptophan (RPT) feeding groups with different doses at 14 g/d and 28 g/d, respectively and 12 cows were in the control group. This approach could avoid dietary tryptophan being degraded by the rumen microorganisms and improve its bioavailability for cows. The results showed that RPT increased milk protein percentage, milk protein yield, milk solid non-fat (SNF), and milk yield. In response to RPT treatment, the levels of melatonin (MT), prolactin (PRL), and insulin-like growth factor-1 (IGF-1) were significantly increased in the serum of cows compared to the controls. RPT feeding improved nutrient utilization efficiency and lactation performance of dairy cows, which enhanced the quality of milk.